Analisis Penerapan Vektor 2D Menggunakan Laboratorium Virtual PhET - Warsih, Dewinta; Malik, Adam (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
Physics explores natural phenomena ranging from everyday experiences to abstract concepts, with vectors being a fundamental component essential for analyzing motion and other physical occurrences. Vectors, defined by their magnitude and direction, are key to describing various phenomena such as force, speed, and acceleration. Utilizing virtual laboratories like PhET offers an excellent opportunity to enhance understanding of vector concepts through interactive simulations. This research focuses on the application of 2D vectors using the PhET virtual laboratory. The research methods include quantitative experiments, where participants engage with vector simulations in a virtual environment. The results indicate that variations in the angle and magnitude of vectors significantly impact the resultant vector's value. These interactive simulations allow for real-time visualization and manipulation of parameters, leading to a deeper comprehension of the subject. Despite some limitations, including the necessity for technological access and the potential for oversimplifying physical phenomena, the benefits of these simulations make them invaluable tools for teaching and research in vector studies. Overall, PhET simulations accelerate the learning process, providing students with a richer and more practical experience to better grasp vector concepts.